Declining and rebounding unhealthy alcohol consumption during the first year of HIV care in rural Uganda, using phosphatidylethanol to augment self‐report. (5th November 2015) - Hahn, Judith A.; Emenyonu, Nneka I.; Fatch, Robin; Muyindike, Winnie R.; Kekiibina, Allen; Carrico, Adam W.; Woolf‐King, Sarah; Shiboski, Stephen
Abstract: Aims: We examined whether unhealthy alcohol consumption, which negatively impacts HIV outcomes, changes after HIV care entry overall and by several factors. We also compared using phosphatidylethanol (PEth, an alcohol biomarker) to augment self‐report to using self‐report alone. Design: A prospective 1‐year observational cohort study with quarterly visits. Setting: Large rural HIV clinic in Mbarara, Uganda. Participants: A total of 208 adults (89 women and 119 men) entering HIV care, reporting any prior year alcohol consumption. Measurements: Unhealthy drinking was PEth+ (≥ 50 ng/ml) or Alcohol Use Disorders Identification Test–Consumption+ (AUDIT‐C+, over 3 months, women ≥ 3; men ≥ 4). We calculated adjusted odds ratios (AOR) for unhealthy drinking per month since baseline, and interactions of month since baseline with perceived health, number of HIV symptoms, antiretroviral therapy (ART), gender and self‐reported prior unhealthy alcohol use. Findings: The majority of participants (64%) were unhealthy drinkers (PEth+ or AUDIT‐C+) at baseline. There was no significant trend in unhealthy drinking overall [per‐month AOR: 1.01; 95% confidence interval (CI) = 0.94–1.07], while the per‐month AORs were 0.91 (95% CI = 0.83–1.00) and 1.11 (95% CI = 1.01–1.22) when participants were not yet on ART and on ART, respectively (interaction P ‐value < 0.01). In contrast, 44% were AUDIT‐C+; the per‐month AORs for being AUDIT‐C+ were 0.89 (95% CI = 0.85–0.95) overall, and 0.84 (95% CI = 0.78–0.91) and 0.97 (95% CI = 0.89–1.05) when participants were not on and were on ART, respectively. Conclusions: Unhealthy alcohol use among Ugandan adults entering HIV care declines prior to the start of anti‐retroviral therapy but rebounds with time. Augmenting self‐reported alcohol use with biomarkers increases the ability of current alcohol use measurements to detect unhealthy alcohol use.